Being Safe in Your Neighborhood - Kesselring, Susan; McGeehan, Dan (Mankato, Minn. : Child's World, 2011)
This fun, colorful book describes basic rules for what to do and what not to do to be safe in your neighborhood.
Includes bibliographical references (p. 24) and index.
Keywords: Safety education -- Juvenile literature; Children's accidents -- Juvenile literature. -- Prevention; Children -- Juvenile literature. -- Crimes against; Safety education; Children's accidents -- Prevention; Children -- Crimes against